Impact of the High-Energy Dynamic Compaction by Multiple Compactors on the Surrounding Environment - Chunlin Jiang; Yanhui Ge; Baoqun Wang; Luchen Zhang; Youbo Liu (Advances in Civil Engineering)
Dynamic compaction machine (DCM) is a widely adopted ground reinforcement technology. However, dynamic compaction energy has a very significant impact on the surrounding environment. At present, the research on the impact of dynamic compaction mainly focuses on the effect of the tamping behavior of a single compactor in the working state, whereas the research on the impact of multiple compactors working jointly is rare. To study the impact of the dynamic compaction energy of multiple compactors working jointly on the surrounding environment, the dynamic response model for multiple compactors working in the same field was established based on the explicit dynamic analysis module in ABAQUS. The validity of the model was verified by comparison with the measured data. Based on this, the impact of the dynamic compaction energy of multiple compactors with different working conditions in terms of the arrangement, spacing, and working time interval was analyzed. The results showed that the arrangement and spacing of the compactors had a remarkable influence on the distribution of the dynamic compaction energy in the surrounding environment. Under the condition of multiple compactors working with a time interval of less than 10 s, the impact of the superimposed dynamic compaction energy due to the interaction of multiple compactors had to be considered.